Cerium(IV)‐Mediated Carbon‐Carbon Bond Formation for the Synthesis of Spirodienone Lactams. Issue 26 (11th July 2022) - Adler, Pauline; Perez, Vincent; Roupnel, Loïc; Fadel, Antoine; Rabasso, Nicolas
Abstract: α‐Phosphorylated para ‐methoxybenzyl allenamides were oxidised with cerium(IV) to produce spirodienone lactams through a 5‐ endo ‐dig cyclisation. By modulating the electronic effects on the phosphorus and nitrogen atoms we were able to overcome some of the limitations of our first‐generation approach. Moreover, replacement of α‐allenylphosphonates with ynamido‐phosphonates led, in two steps, to the same spirodienone core after oxidation with cerium(IV) hence overcoming other limitations of the previous method. Abstract : Spirodienone lactams were prepared from the oxidation of α‐amino allenylphosphonates or ynamido‐phosphonates. The limitations observed for this synthesis were addressed by changing the nature of phosphorylated moiety.